Diagnostic Performance and Reliability of Non-Enhanced Imaging Characterization Quotients for the Differentiation of Infectious and Malignant Pulmonary Nodules in Hematological Patients Using 3T MRI - Nagel, Sebastian Niko; Kim, Damon; Wylutzki, Tatjana; Steffen, Ingo G.; Schwartz, Stefan; Penzkofer, Tobias; Hamm, Bernd; Elgeti, Thomas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To evaluate the diagnostic performance and reliability of non-enhanced imaging characterization quotients (NICQs) derived from magnetic resonance imaging (MRI) in the differential diagnosis of pulmonary nodules in hematological patients.Materials and Methods A total of 83 lesions in 45 consecutive hematological patients were analyzed (10 bacterial pneumonias, 16 fungal pneumonias, 19 pulmonary lymphoma manifestations). The MRI protocol included T2-weighted single-shot fast spin echo (FSE) and T1-weighted gradient echo (GRE) sequences. T2-based T2-NICQmean and T2-NICQ90th were calculated from signal intensities measured in the lesion, muscle, and fat ((SILesion – SIMuscle)/(SIFat – SIMuscle) * 100), and simple T1-based T1-Qmean from signal intensities of the lesion and muscle (SILesion/SIMuscle). Images were read by one radiologist with > 7 years and one with 1 year of experience. For statistical evaluation the Kruskal-Wallis or Mann-Whitney U-test, receiver operating characteristic (ROC) analysis with calculation of areas under the curve (AUC), and intraclass correlation coefficients (ICCs) were used.Results Medians of T2-NICQs differed significantly when comparing infectious lesions and lymphoma manifestations in general (T2-NICQmean 20.33 vs. 10.14; T2-NICQ90th 34.96 vs. 25.52) or fungal lesions and lymphoma manifestations in particular (T2-NICQmean 19.00 vs. 10.14; T2-NICQ90th 34.49 vs. 25.25). The AUCs for T2-NICQs on the per-patient level ranged from 0.73 to 0.79. ICCs were at least > 0.85, except for intrarater testing of T2-NICQ90th (0.79).Conclusion The overall diagnostic performance of T2-NICQs is adequate for differentiating infectious and fungal lesions from lymphoma manifestations. The results show good to excellent intra- and interrater agreement. We therefore consider NICQs helpful in the diagnostic workup of pulmonary nodules in hematological patients.Key points: Citation Format
Keywords: thorax; diagnostic radiology; infection; lymphoma; MR imaging